2020
DOI: 10.1101/2020.06.28.176065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nf2 fine-tunes proliferation and tissue alignment during closure of the optic fissure in the embryonic mouse eye

Abstract: Uveal coloboma represents one of the most common congenital ocular malformations accounting for up to 10% of childhood blindness (1~ in 5,000 live birth). Coloboma originates from defective fusion of the optic fissure (OF), a transient gap that forms during eye morphogenesis by asymmetric, ventral invagination. Genetic heterogeneity combined with the activity of developmentally regulated genes suggest multiple mechanisms regulating OF closure. The tumor suppressor and FERM domain protein neurofibromin 2 (NF2) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 127 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…To detect proliferating cells, pregnant dams received one intraperitoneal EdU injection two hours before sacrificing (30 µg/g; Thermofisher/Invitrogen; #E10187). Male embryos with conditional deletion of Porcn (hereafter Porcn CKO ) and control littermates were processed as previously published (Sun et al, 2020). For antigen retrieval, cryostat sections were treated with 1% Triton X-100 or hot citrate buffer (pH 6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect proliferating cells, pregnant dams received one intraperitoneal EdU injection two hours before sacrificing (30 µg/g; Thermofisher/Invitrogen; #E10187). Male embryos with conditional deletion of Porcn (hereafter Porcn CKO ) and control littermates were processed as previously published (Sun et al, 2020). For antigen retrieval, cryostat sections were treated with 1% Triton X-100 or hot citrate buffer (pH 6).…”
Section: Methodsmentioning
confidence: 99%
“…Mouse lines were maintained on a mixed genetic C57BL/6 and CD-1 background. For temporally controlled Porcn inactivation, a conditional Porcn allele, tamoxifen-inducible, ubiquitous Gt(ROSA)26Sor tm1(cre/ERT)Nat (hereafter ROSA26 CreERT ) and the recombination reporter RosaR26 were utilized, with established genotyping protocols or Transnetyx (Cordova, TN) using Taqman with custom-designed primers (Badea et al, 2003; Bankhead et al, 2015; Barrott et al, 2011; Soriano, 1999; Sun et al, 2020). Noon of the day with an observed vaginal plug was counted E0.5.…”
Section: Methodsmentioning
confidence: 99%
“…This fissure allows the necessary vasculature to enter and support the eye during development 15,17,22,23 . With further growth, the margins of the optic fissure become apposed and ultimately merge to complete optic fissure closure by E12.5 (Figure 1C) 22,24 . Subsequently, other tissues of the eye develop from the surrounding mesenchyme and melanocytes from the neural crest enter to populate the uveal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Horsford et al 20 found that Mitf deficiency in OV cultures generates ectopic neural retina tissue, whereas the ectopic expression of Mitf shifted the fate of OV cells from a neural retina phenotype to an RPE phenotype 20 . Furthermore, the failure to exclude Mitf from the margins of the optic fissure led to upregulated RPE fate and failed optic fissure closure, thus highlighting the importance of maintaining specific Mitf expression levels and boundaries during ocular development 24 .…”
Section: Introductionmentioning
confidence: 99%